2021
DOI: 10.1111/ivb.12311
|View full text |Cite
|
Sign up to set email alerts
|

Knots, spoons, and cloches: DNA barcoding unusual larval forms helps document the diversity of Neotropical marine annelids

Abstract: The morphological diversity of marine annelid larvae is stunning. Although many of the larval forms have been categorized as trochophores or modified trochophores, there are a few groups with distinctive larval features that make them easy to distinguish from other annelid larvae. We collected 252 annelid larvae from the plankton, with particular emphasis on oweniids, polygordiids, and thalassematids (i.e., echiurans) and sequenced fragments of their cytochrome c oxidase subunit 1 and 16S ribosomal RNA genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…In a pioneering study, Barber and Boyce [7] found that only 50% of the gonodactyloid stomatopod larval operational taxonomic units (OTUs) collected in the Coral Triangle could be matched to adults, despite having reference sequences for more than 90% of the known species from the region. Studies focused on planktonic stages in less well-studied regions, or of understudied groups like hemichordates, phoronids or certain families of polychaetes, report similar or greater match discrepancies, likely due to poor sampling of the adult fauna [8][9][10][11][12]. However, even studies that include both life stages report larvae for which the adult forms have not been detected [13,14] or were not sampled at the same site [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a pioneering study, Barber and Boyce [7] found that only 50% of the gonodactyloid stomatopod larval operational taxonomic units (OTUs) collected in the Coral Triangle could be matched to adults, despite having reference sequences for more than 90% of the known species from the region. Studies focused on planktonic stages in less well-studied regions, or of understudied groups like hemichordates, phoronids or certain families of polychaetes, report similar or greater match discrepancies, likely due to poor sampling of the adult fauna [8][9][10][11][12]. However, even studies that include both life stages report larvae for which the adult forms have not been detected [13,14] or were not sampled at the same site [15].…”
Section: Introductionmentioning
confidence: 99%